Association of PIT-1 gene polymorphism with milk production traits in Sahiwal cattle - CHAUHAN, ANKUR; TIWARI, MADHU; SINGH, SATYENDRA PAL; SHARMA, DEEPAK; KUMAR, SUMIT; GOEL, RAKESH; BHATTACHARYA, AMITAV; SINGH, VIJAY (The Indian Journal of Animal Sciences, 2015)
In the present study, identification of PIT-1 gene polymorphism and its association with milk production traits was undertaken in 77 Sahiwal cattle maintained at NDRI, Karnal using PCR-RFLP. Amplification of DNA sample revealed 600 bp product and restriction digestion with HinfI showed three types of genotypes, namely, AA (600bp), AB (600, 343 and 257 bp) and BB (343 and 257 bp) genotypes. The frequency of BB genotypes was highest (64.98%) in all screened samples, followed by AB genotype (31.16%) and AA genotype (3.89%). The allelic frequency of PIT-1 A and B alleles were 19.48% and 80.51%, respectively. Association studies of PIT-1 gene with milk production traits showed that age at first calving, gestation period and lactation period had non-significant variation among all the 3 genotypes up to fourth lactation. However, a significant difference was found among the 3 genotypes for total milk yield and milk yield at 300 days with AA genotype showing higher value than AB and BB genotypes in the first lactation. From present investigation, the HinfI /PCR-RFLP revealed polymorphic pattern of PIT-1 gene in Sahiwal cattle and association studies showed significant effect of A allele on milk production.